Institutional Care for Long-Term Mechanical Ventilation in Canada: A National Survey - Louise Rose; Douglas McKim; Sherri Katz; David Leasa; Mika Nonoyama; Cheryl Pedersen; Monica Avendano; Roger Goldstein (Canadian Respiratory Journal, 2014)
INTRODUCTION: No national Canadian data define resource requirements and care delivery for ventilator-assisted individuals (VAIs) requiring long-term institutional care. Such data will assist in planning health care services to this population.